A two state proactive transport protocol for satellite based networks - Sarkar M.; Shukla K.K.; Dasgupta K.S. (My University, 2025)
In satellite-based networks, current TCP Protocols have lower throughput performance mainly due to the effect of long propagation delays and high link error rates. In this paper, a new congestion control protocol for satellite-based networks is proposed. The protocol uses a proactive approach and is composed of novel ideas like Proactive Slow Start, Proactive Congestion Avoidance and Decision based Error handling policies that are combined with traditional TCP algorithms, like Fast Retransmit. The mainstay of our protocol is the nature of the RTT pattern can give us indication of an incipient congestion in the network. This changing pattern of RTT is used to differentiate between congestion and link error, thus avoiding unnecessary rate throttle. In the initial phase, necessary augmentation of ns2 simulator pertaining to the proposed protocol has been carried out. This was essential to create a necessary test bed for exhaustive simulation of the protocol considering a GEO network, with different congestion level and packet error rate. Simulation results show that the protocol always outperforms other TCP protocols in terms of goodput and an improvement of 80% to 120% is observed, especially when the packet error rate is very high. Evaluation of the protocol shows a high fairness property and excellent adaptability to high levels of congestion and channel errors. Copyright © 2012 - All Rights Reserved.